2022
DOI: 10.1177/09691413221109999
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of alternative technologies compared with faecal immunochemical test and/or colonoscopy in colorectal cancer screening: A systematic review

Abstract: Objective Colorectal cancer (CRC) is the third most common cancer and the second largest cause of cancer-related death worldwide. Current CRC screening in various countries involves stool-based faecal immunochemical testing (FIT) and/or colonoscopy, yet public uptake remains sub-optimal. This review assessed the literature regarding acceptability of alternative CRC screening modalities compared to standard care in average-risk adults. Method Systematic searches of MEDLINE, EMBASE, CINAHL, Cochrane and Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Low levels of screening participant tolerance for bowel preparation led to suggestions for alternate methods of screening, such as blood tests. Research into alternative technologies for screening, such as multicancer early detection tests [ 24 , 25 ] and the acceptability of new technologies for bowel cancer (including blood tests and pill‐cameras) [ 26 ] is ongoing elsewhere. These research areas should ensure the representation of people with a variety of health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of screening participant tolerance for bowel preparation led to suggestions for alternate methods of screening, such as blood tests. Research into alternative technologies for screening, such as multicancer early detection tests [ 24 , 25 ] and the acceptability of new technologies for bowel cancer (including blood tests and pill‐cameras) [ 26 ] is ongoing elsewhere. These research areas should ensure the representation of people with a variety of health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the financial aspect, the other downsides of screening, such as patient anxiety and lead-time bias, will all need to be considered seriously. Most of the existing studies examining the attitude and preference for blood-based CRC tests were conducted in Western societies [ 26 , 27 ]. Preference of the technology in Asia is understudied.…”
Section: Discussionmentioning
confidence: 99%
“…Such profiling efforts can inform the crafting of targeted screening programs to cater to the heterogeneous preferences across different groups. Fourth, many preference studies were done in Western countries and very few were done in Asia [ 26 , 27 ]. Cultural and social norms could influence decision-making and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized, controlled trial also reported significant effects of colonoscopy examination in reducing CRC risk (RR = 0.69) and mortality (RR = 0.50) [219]. Colonoscopy may be considered as the only CRC screening modality for specific (high-risk) populations or may be used in combination with other non-invasive modalities in general (average-risk) populations [220][221][222].…”
Section: Colonoscopymentioning
confidence: 99%